Formulation and Evaluation of Propolis Loaded Nanosponges Based Topical Anti-Inflammatory Gel - Ratnaparkhi, Mukesh P.; Kshirsagar, Swati Dattatray (Indian Journal of Pharmaceutical Education and Research, 2025)
Objectives: To develop and evaluate a Propolis-Loaded Nanosponge (PLN)-based topical gel with potential anti-inflammatory, antifungal and antibacterial activities. Materials and Methods: PLNs were prepared using the emulsion solvent diffusion method with Ethyl Cellulose (EC) and Polyvinyl Alcohol (PVA) as key components. Various parameters, including particle size, Polydispersity Index (PDI), zeta potential, entrapment efficiency, production yield and drug release profile, were analyzed to determine the optimal formulation. Physicochemical characteristics were analyzed using FTIR, DSC, SEM and XRD. The optimized PLN was incorporated into a 2% w/w topical gel and further characterized for pH, viscosity, spreadability, drug content, in vitro drug diffusion, ex vivo skin penetration, antifungal, antibacterial activity and stability. Results: The optimized PLN showed high drug encapsulation efficiency and compatibility with the polymer. The formulated 2% w/w PLN-based gel exhibited significant in vitro drug diffusion (90.43%) and ex vivo skin penetration (79.82%) within 4 hr. It demonstrated potent antifungal and antibacterial activities. In vivo anti-inflammatory studies revealed that the gel provided comparable anti-inflammatory efficacy to standard 2% Diclofenac gel. Conclusion: The Propolis-loaded nanosponge-based gel demonstrated promising results, including effective drug delivery, antimicrobial activity and comparable anti-inflammatory performance to standard treatments, making it a potential topical therapeutic agent.
Keywords: Emulsion Solvent Diffusion Method; In vivo Anti-Inflammatory Study; Nanosponges; Propolis; Topical Gel